Posthatch morphometrical changes in the Spleen of Chabro Birds - Singh, S.P.; Verma, Abhinov; Pathak, Archana; Prakash, Ajay; Farooqui, MM (Indian Journal of Veterinary Anatomy, 2023)
Gross morphometrical observations were made on developing spleen of thirty apparently healthy Chabro birds irrespective of the sex. For this purpose the birds of known age were procured from University poultry farm of U.P. Pandit Deen Dayal Upadhayaya Pashu Chikitasa Vigyan Vishwavidhyala evam Go Anusandhan Sansthan Mathura.All the birds for the study were selected at the time of hatching and were grown in a separate portion of the same poultry farm. These were sacrificed at 0, 30, 60, 90 and 150 days after hatching. The mean body weight, spleen weight and diameter during post hatch life were recorded. There were significant increase in the body weight, weight and diameter of the spleen with advancement of age in different group.